Validating a smart nutrient solution replenishment strategy to save water and nutrients in hydroponic crops - Neocleous, Damianos; Savvas, Dimitrios (Frontiers in Environmental Science, 2022)
Sustainable use of water and nutrients is fundamental in modern Mediterranean greenhouses and the use of modern decision support systems (DSS) can contribute to this direction. This work focuses on implementing new elements in water and nutrient recycling in cropping systems under saline conditions. Thus, two nutrient solution (NS) control strategies were applied to tomato crops grown in a recirculated NS under low- and high-salinity (NaCl) conditions. According to the first strategy, (i.e., Standard-STD) NS was replenished with water and nutrients based on predetermined ‘uptake concentrations’ (UCs), i.e. nutrient to water uptake ratios, following standard commercial practices. According to the second strategy, NS was replenished by applying recalculated UCs of all nutrients after chemical analysis of a drainage solution sample using the software NUTRISENSE (NTS). Compared with the STD strategy, tomato plants treated with NTS retained drainage nutrient concentrations closer to the optimal values irrespectively of the salinity treatment. This eventually accounted for a smaller deviation from the mean threshold salinity value in the root zone at higher salinity levels, thus plants retained water consumption and crop yield potential at higher stomatal conductance minimizing physiological impacts of salinity on plants. Nutritional control strategies did not impose substantial difference in the UCs for most of the nutrients; however, this was not the case under salinity. Nutrient UCs determined and NTS strategy can be successfully used in DSS to optimize nutrient supply and prolong recirculation, thereby saving precious water and nutrients, in Mediterranean hydroponic crops with particular emphasis on saline environments.